The Dimensional Depth of Words: Vocabulary Knowledge and Reading Comprehension - Súsanna Björg Vilhjálmsdóttir 1971- (2015)
Grasping the multi-dimensional aspects of word knowledge is a gradual and challenging facet of language acquisition for any learner. The ability to effectively read in today´s society is closely associated with learners´ educational prospects and later their likelihood of obtaining a good job. However, our contemporary computerized and globalized world demands that we gain these skills in English as well as in our first language. As the linguistic environment in Iceland has transformed considerably, Icelandic learners find the need to acquire reading proficiency in English. In evaluating their proficiency level, their overall vocabulary knowledge needs to be measured to address problematic proficiency gaps that may emerge due to morphological, semantical and syntactical differences. By using authentic native tests and various testing tools for credibility, their general receptive vocabulary breadth, productive depth, and overall comprehension of English material can be evaluated. The following pilot study investigates four tenth graders´ vocabulary size, the size-depth relationship and how their size-depth vocabulary knowledge influences their comprehension of authentic written material. Three tests are applied in distinguishing the participants´ proficiency; Meara´s and Milton´s X-Lex (2003) vocabulary test to measure the breadth of vocabulary, Paribakht´s and Wesche´s (1993) Vocabulary Knowledge Scale (VKS) to measure vocabulary depth and a native English comprehension test taken from a California Standard Test (2009) (CST) to evaluate the size-depth relationship on comprehension. The results revealed that although the participants considered themselves to have an adequate breadth of vocabulary knowledge, their overall depth of knowledge was insufficient as particular components of word knowledge affected their outcomes. Based on the results, the study presents vital information about the importance of L2 learners acquiring adequate word knowledge and connecting multi-dimensional components of depth with their ...